Complaint and politeness strategies used by Iranian speakers of English - Masjedi, Narges; Paramasivam, Shamala (Australian International Academic Centre, 2018)
Complaint is a face threatening act and it happens when a speaker reacts with anger to things which go wrong or to a speech or an action which affected him/her unfavorably. Therefore, complaints can engender social relationship breakdown. However, a complainer can use politeness when he/she aims to maintain a good relationship with complainee or to mitigate the severity of his/her complaint and face threat. This study aims to investigate the complaint speech act with regard to the strategies and structure used as well as the politeness strategies employed by Iranian learners in communication with other nationalities in the academic context of a university. Searle’s (1969) speech act theory and Brown and Levinson’s (1987) politeness theory comprised the theoretical framework of the study. The data were elicited through open-ended discourse completion task questionnaire from 50 Iranian learners. The data were analyzed using pragmatics as the approach within discourse analysis. The findings show that Iranians are able to draw on a variety of strategies and structures and adapt them in a flexible manner when faced with various complaint-provoking situations. Culturally, the findings show that Iranians are indirect and exercise negative politeness as they try to minimize the face threatening act of complaining. However, when the situation demands for it, they can be direct in their manner of speech.